2019
DOI: 10.1039/c9sc01513b
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoordinate iodine for catalytic asymmetric diamination of styrene: insights into the mechanism, role of solvent, and stereoinduction

Abstract: Stereoselectivity in the asymmetric diamination of styrene catalyzed by chiral hypercoordinate iodine originates from the prochiral face recognition when the substrate binds to the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 74 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…The results showed that M06-2X calculated reaction barriers agree best with the experimentally derived values, with an error of less than 1 kcal/mol for both pathways (see Figure S1 and Tables S1 and S2 for detail). This is in agreement with previous computational studies from our group and others that the M06-2X method calculates kinetics and thermodynamics data close to experiments and is a suitable method to study organocatalytic reactions with multiple noncovalent interactions. , …”
Section: Computational Methodologysupporting
confidence: 91%
“…The results showed that M06-2X calculated reaction barriers agree best with the experimentally derived values, with an error of less than 1 kcal/mol for both pathways (see Figure S1 and Tables S1 and S2 for detail). This is in agreement with previous computational studies from our group and others that the M06-2X method calculates kinetics and thermodynamics data close to experiments and is a suitable method to study organocatalytic reactions with multiple noncovalent interactions. , …”
Section: Computational Methodologysupporting
confidence: 91%
“…Catalytic vicinal diamination of terminal styrenes was carried out in 3:1 MTBE/HFIP, whereas a 2:1 mixture of MTBE/TFE worked better for internal styrenes. In an effort to determine the source of stereoinduction for this hypercoordinate iodine-catalyzed vicinal diamination of styrenes, Sunoj and co-workers employed computational methods to investigate the mechanism of this transformation and to elucidate the role of HFIP on the reaction pathway (Scheme b) using an achiral hypercoordinate iodine species . Subsequently, the factors affecting the stereoinduction were delineated by examining the chiral hypercoordinate iodine species in the mechanism.…”
Section: Hypervalent Iodine Chemistrymentioning
confidence: 99%
“…Notable asymmetric reactions developed include α-functionalization of ketones, difunctionalization of alkenes, oxidative dearomatization of phenols, and many others . However, stereochemical models and mechanistic discussions of these transformations are still in their infancy.…”
Section: Introductionmentioning
confidence: 99%